VD_FINDINFO Jug / 2024 / 359 vom 12. April 2024 - VD Tribunal cantonal (2024)
MISE EN ACCUSATION, PRINCIPE DE L'ACCUSATION, ACQUITTEMENT | 130 LATC, 324 CPP (CH), 325 al. 1 CPP (CH), 329 CPP (CH), 429 CPP (CH), 430 CPP (CH), 9 CPP (CH)